Reading-Concept Map pada Pembelajaran Numbered Head Together (NHT) untuk Meningkatkan Hasil Belajar Biologi Siswa - Sura, Yoel; Syamsiah, Syamsiah; Bahri, Arsad (Universitas Negeri Makassar, 2020)
Abstract. This research aims to determine whether there is influence of the Remap Coople NHT model on student learning outcomes. The independent variables in this study are Remap Coople NHT and direct instructional learning with lecture method, while the dependent variable is learning outcomes of students. The population in this study were all students of class XI MIA SMA Negeri 1 Palopo which consisted of 6 classes. The research sample was selected by random sampling technique, namely XI MIA 1 as an experimental group with 30 students and XI MIA 2 as a control group with 30 students. Data retrieval method is by using a written test in the form of multiple choice questions totaling 20 numbers in accordance with the learning objectives. The collected research were analyzed using descriptive statistics and inferential statistics. The results showed that there was an effect of the application of the Remap Coople NHT model on the learning outcomes of students in SMA Negeri 1 Palopo.Â Keywords: remap coople nht, direct instructional, learning outcomes